Agroforestry practices for physiological amelioration of salt aff ected soils - Manas Ranjan Nayak, Dhiraji Patel, Abhishek Mehta, Satish Kumar Sinha, Rajesh Gunaga, Laxmikanta Behera* (Journal of Plant Stress Physiology, 2015)
Agroforestry is a sustainable land use system act as an alternative form of biological reclamation in salt affected soils apart from sustainable production, continuous income, and regular employment along with food and nutrition security. In general, salt affected soils get ameliorated by tree species; however, following factors such as nature and type of tree species planted, growth habit, quantity and quality of litter production, planting density, nitrogen fixation, and different management practices are influenced. In the present study, various studies pertaining to soil reclamation in the salt affected soils are reviewed. Overall result showed that trees grown with crops, horticultural crops, pastures resulted in improvement of physical and chemical properties of soil under various agroforestry systems. For instance, reduction of soil pH, electrical conductivity, and exchangeable sodium percentage minimization of salt deposition in the upper layers of the soil, improvement of water permeability and water holding capacity, improvement of infiltration rate and hydraulic conductivity with soil fertility, enhancement of cation exchange capacity, and other features are characteristics of soil as influenced by tree species, as well as through agroforestry practices. Various multipurpose tree species such as Acacia auriculiformis, Acacia nilotica, Albizia lebbeck, Terminalia arjuna, Casuarina equisetifolia, Prosopis cineraria, Prosopis juliflora; and fruit trees such as Zizyphus jujuba, Emblica officinalis, Syzygium cumini, and Tamarindus indica ameliorated the different salt affected soils in different agroforestry systems viz., agrisilvicultural system, silvipastoral system, multipurpose wood lot, and agrihorisilvicultural system. Thus, agroforestry system provides an alternative for restoring soil health and amelioration of salt affected soils for further yield improvement. Therefore, these species are suggested for reclamation of salt affected soil through agroforestry systems.